Impact of T cells on neurodegeneration in anti‐GAD65 limbic encephalitis. Issue 12 (28th November 2021) - Dik, Andre; Widman, Guido; Schulte‐Mecklenbeck, Andreas; Witt, Juri‐Alexander; Pitsch, Julika; Golombeck, Kristin S.; Wagner, Jan; Gallus, Marco; Strippel, Christine; Hansen, Niels; Mönig, Constanze; Räuber, Saskia; et al.
Abstract: Objective: Direct pathogenic effects of autoantibodies to the 65 kDa isoform of glutamic acid decarboxylase (GAD65) in autoimmune limbic encephalitis (LE) have been questioned due to its intracellular localization. We therefore hypothesized a pathogenic role for T cells. Methods: We assessed magnet resonance imaging, neuropsychological and peripheral blood, and CSF flow cytometry data of 10 patients with long‐standing GAD65‐LE compared to controls in a cross‐sectional manner. These data were related to each other within the GAD65‐LE group and linked to neuropathological findings in selective hippocampectomy specimen from another two patients. In addition, full‐resolution human leukocyte antigen (HLA) genotyping of all patients was performed. Results: Compared to controls, no alteration in hippocampal volume but impaired memory function and elevated fractions of activated HLADR + CD4 + and CD8 + T cells in peripheral blood and cerebrospinal fluid were found. Intrathecal fractions of CD8 + T cells negatively correlated with hippocampal volume and memory function, whereas the opposite was true for CD4 + T cells. Consistently, antigen‐experienced CD8 + T cells expressed increased levels of the cytotoxic effector molecule perforin in peripheral blood, and perforin‐expressing CD8 + T cells were found attached mainly to small interneurons but also to large principal neurons together with wide‐spread hippocampal neurodegeneration. 6/10 LE patients harbored the HLA‐A*02:01 allele known to present the immunodominant GAD65114–123 peptide in humans. Interpretation: Our data suggest a pathogenic effect of CD8 + T cells and a regulatory effect of CD4 + T cells in patients with long‐standing GAD65‐LE.